A rapid and sensitive diagnosis of bovine leukaemia virus infection using the nested shuttle polymerase chain reaction - González, Ester Teresa (1999)
Bovine leukaemia virus (BLV) is the causative agent of enzootic bovine leukosis (EBL). In Argentina, where a program to eradicate EBL has been introduced, sensitive and reliable diagnosis has attained high priority. Although the importance of the agar gel immunodiffusion test remains unchanged for routine work, an additional diagnostic technique is necessary to confirm cases of sera with equivocal results or of calves carrying maternal antibodies. Utilizing a nested shuttle polymerase chain reaction, the proviral DNA was detected from cows experimentally infected with as little as 5 ml of whole blood from BLV seropositive cows that were nonetheless normal in haematological terms. It proved to be a very sensitive technique, since it rapidly revealed the presence of the provirus, frequently at 2 weeks postinoculation and using a two-round procedure of nested PCR taking only 3 hours. Additionally, the primers used flanked a portion of the viral genome often employed to differentiate BLV type applying BamHI digestion. It is concluded that this method might offer a highly promising diagnostic tool for BLV infection.